Perbedaan Kualitas dan Pertumbuhan Benih Edamame Varietas Ryoko yang Diproduksi di Ketinggian Tempat yang Berbeda di Lampung - Hakim, Nurman Abdul (Jurnal Penelitian Pertanian Terapan, 2013)
Nurman Abdul Hakim: Perbedaan Kualitas dan Pertumbuhan Benih Edamame Varietas Ryoko? Volume 13, Nomor 1, Januari 2013 9 1, 2, and 3 weeks, it is seen that the seeds produced in the Highlands of generating plant weights heavier than seed produced in the lowlands. Keywords: : seeds edamame, altitude place, seed qualityThis research aims to know the difference in the quality of the seeds and the growth of the edamame is augmented at an altitude of different places. In addition, to find out whether the height effect on physiological properties of the seed varieties edamame Ryoko. Planting edamame made in May ? August 2012 simultaneously in two locations: in the Highlands (West Lampung, Sekincau) and in the lowlands (the practice of lampung State Polytechnic). Edamame seeds that are produced in both places are then tested in the laboratory of food crops. and in Lampung State Polytechnic. Seed quality testing is done using the complete randomized design and is repeated 5 times. The observations showed that seed produced in the Highlands (West Lampung, Sekincau) looks greener than seed produced in the lowlands (Lampung State of Polytechnic). When compared on the basis of the size of the seed, then it looks also that seed produced in the Highlands, are smaller. Weight of 100 seeds of grain produced in the Highlands of lighter (26.8 g) than the seed resulting from the lowlands (36.4 g). The test results obtained through the analysis of statistics that the percentage of seed sprouts power resulting from the planting in high places better (79%) than from planting in lowlands (73.2%). Look also that the seed resulting from the planting of high-yield abnormal smaller sprouts (16%) than are generated in a low place (22.4%). The results of testing the levels of protein and fat which is done in the laboratory of Agricultural Technology Lampung State Polytechnic obtained that protein levels are the second seeds at the height of the place is no different, which is around 36%. While the fat content of seeds produced in the Highlands of 13.8%, lower than the seeds that are produced in the lowlands which amounted to 15.8%. The observations of plant height at the age of 1, 2, and 3 weeks, looks that seed produced on the highlands produces plant growth higher than seed produced in the lowlands. The results of observation of the number of leaves of plants at the age of 1, 2, and 3 weeks, it looks that the seed resulting in the Highlands and the lowlands produced the same number of leaves on the plant young edamame. Result observation of plant age on edamame weights of